2022
DOI: 10.1007/s00586-022-07194-y
|View full text |Cite
|
Sign up to set email alerts
|

SPINE20 recommendations 2021: spine care for people’s health and prosperity

Abstract: Purpose The focus of SPINE20 is to develop evidence-based policy recommendations for the G20 countries to work with governments to reduce the burden of spine disease, and disability. Methods On September 17–18, 2021, SPINE20 held its annual meeting in Rome, Italy. Prior to the meeting, the SPINE20 created six proposed recommendations. These recommendations were uploaded to the SPINE20 website 10 days before the meeting and opened to the public for comments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…In terms of the importance of exercise in the elderly population, SPINE20 which is an international advocacy group, called to G20 leaders and published a recommendation for the G20 countries to adopt a strategy to promote daily physical activity and exercises among the elderly population to maintain an active and independent life with a healthy spine, particularly since COVID‑19 pandemic [ 25 ]. Our results indicated that regular exercise was decreased in 30% of the elderly population since the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the importance of exercise in the elderly population, SPINE20 which is an international advocacy group, called to G20 leaders and published a recommendation for the G20 countries to adopt a strategy to promote daily physical activity and exercises among the elderly population to maintain an active and independent life with a healthy spine, particularly since COVID‑19 pandemic [ 25 ]. Our results indicated that regular exercise was decreased in 30% of the elderly population since the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of SPINE20 is to develop evidence-based policy recommendations for the G20 governments to reduce the burden of spine disorders, disability, and injuries. [7,8] The recommendations are intended to benefit individuals with spine disorders, benefiting the community and, ultimately, the country. Countries have different abilities to implement recommendations depending on their geographical location and wealth.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, evidence for the effectiveness of MAs in the care of patients with spinal disabilities is not well established. 4 Degenerative cervical myelopathy (DCM) is the leading cause of spinal cord impairment worldwide; the prevalence is estimated at a minimum of 605 per million in North America. 5 Chronic cervical spinal cord compression leads to neurological symptoms, functional impairment, and deterioration of quality of life (QOL).…”
mentioning
confidence: 99%
“…For example, in cancer treatment, considerable high-level evidence for the effectiveness of MAs has been accumulated, and the concept has been fully endorsed by cancer organizations 1–3 . However, evidence for the effectiveness of MAs in the care of patients with spinal disabilities is not well established 4 …”
mentioning
confidence: 99%